Metal accumulation capacity of raphidascaridid nematode, Hysterothylacium reliquens, infecting the king soldier bream (Argyrops spinifer) - Hanadi B. Baghdadi; Rewaida Abdel-Gaber; Saleh Al Quraishy; Marwa M. Abou Hadied; Tahani Al-Otaibi; Manal F. Elkhadragy; Esam M. Al-Shaebi; Mohamed Dkhil (Journal of King Saud University: Science, 2023)
There are several types of biological markers in the environment. The potential parasites’ ability to serve as bio-indicators of pollution in marine ecosystems was the focus of the current study. Forty samples of the king soldier bream Argyrops spinifer, were collected from the Red Sea (Jeddah, Saudi Arabia) for this study, and they were examined for parasite infections. Only 25 fish samples included one naturally occurring nematode parasite, Hysterothylacium reliquens, which had three of its life-cycle stages (adults, L3, and L4 larvae). The levels of some metals (Fe, Cu, Cd, and Pb) were detected in the parasite stages and the tissues of the fish host tissues (liver, muscle, and intestine). These metals accumulated higher in non-infected fish tissues than in infected ones. The significant parasite capability for metal accumulation rather than fish tissues was validated by bioconcentration factors. Depending on the stage of a parasite’s life, different metals were used. Larval stages are more prone to gathering essential elements (Fe and Cu). Although adults have a greater tolerance to toxic metals (Cd and Pb). The various metal absorption mechanisms were referred to as the differences between parasite stages. This proved that fish nematodes might serve as helpful bioindicators for assessing the extent of heavy metal contamination of aquatic ecosystems.